Thirty-three new species of water beetles in the genus Hydraena Kugelann from Cameroon (Coleoptera: Hydraenidae) - Perkins, Philip D. (Zootaxa, 2022)
Thirty-three new species of Cameroonian water beetles in the genus Hydraena Kugelann are described, based on the examination and databasing of 355 specimens from 19 localities/events. Male genitalia are illustrated, and high resolution habitus images of the holotypes are provided, as are distribution maps. The following new species of Hydraena are described: H. cameroancylis, H. cameroarida, H. camerobuloba, H. camerocameola, H. camerocarinata, H. cameroclandestina, H. camerocompacta, H. camerocomplexa, H. camerocompressa, H. cameroconcava, H. cameroconfinis, H. camerocontinua, H. camerocontrasta, H. cameroconvexa, H. camerocordata, H. camerocorona, H. camerocrebrata, H. camerocubita, H. camerocurvata, H. camerodidacta, H. camerodigita, H. cameroflagellata, H. camerofoveata, H. camerojocula, H. camerolatula, H. cameroovala, H. cameropalmula, H. cameropetila, H. cameroradiata, H. camerosemicordata, H. camerosetosa, H. camerosicula, and H. millenaria.